Communication Strategy the Ministry of Villages, Developmentof Disadvantaged Regions and Transmigrationin the Village SDGs Goals - Dinda Rosanti Salsa Bela (CV. Abhinaya Indo Group, 2025)
The purpose of this research is to look at the Village SDGs in Accelerating the Achievement of Sustainable National Goals in development with regional autonomy. The focus of this research is the effectiveness of disseminating information through social media in conveying the Village SDGs. This study seeks to answer the substance: development communication strategies used by the Ministry of Village Questions, Development of Disadvantaged Regions and Transmigration in communicating village SDGs. The data for this research is the official Twitter content of the official account of the Ministry of Villages, Development of Disadvantaged Regions and Transmigration (@kemendespdtt). The Nvivo 12 plus in this study are graph analysis, cluster analysis, and word cloud analysis. The data that has been displayed is submitted using qualitative analysis methods. The data used by the researcher is data that displays hashtags, mentions, chart hierarchies, and word clouds. The data is then processed with Microsoft Excel tools to get the results displayed in the form of percentages. The results of this study show that the communication built by @kemendespdtt in communicating the Village SDGs through hashtags and mentions is about achievement programs, activities to the Kemendes PDTT campaign in the SDGs Village goals. Kemendes PDTT conveys information openly in accordance with the objectives to be achieved, especially in terms of campaigning for the Village SDGs. Disseminating information through social media is the easiest and most effective way to reach everyone.